2012
DOI: 10.1371/journal.pone.0037027
|View full text |Cite|
|
Sign up to set email alerts
|

A Tale of Many Cities: Universal Patterns in Human Urban Mobility

Abstract: The advent of geographic online social networks such as Foursquare, where users voluntarily signal their current location, opens the door to powerful studies on human movement. In particular the fine granularity of the location data, with GPS accuracy down to 10 meters, and the worldwide scale of Foursquare adoption are unprecedented. In this paper we study urban mobility patterns of people in several metropolitan cities around the globe by analyzing a large set of Foursquare users. Surprisingly, while there a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
407
1
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 517 publications
(452 citation statements)
references
References 33 publications
(51 reference statements)
15
407
1
11
Order By: Relevance
“…Work such as [3] provides an analysis of tracking the mobility of phone users to show that humans do not have random trajectories but have both temporal and spatial regularities. Further researches by [12] and [13] experiment with data from different scales and datasets from various metropolitan areas, and show that different cities can have variances in human mobility patterns. A recent work by [4] showed that call data records can be organized into profiles and clustered using the spatiotemporal usage characteristics of each profile, allowing for accurate prediction and possible adaptation of the network according to the usage dynamics.…”
Section: Related Workmentioning
confidence: 99%
“…Work such as [3] provides an analysis of tracking the mobility of phone users to show that humans do not have random trajectories but have both temporal and spatial regularities. Further researches by [12] and [13] experiment with data from different scales and datasets from various metropolitan areas, and show that different cities can have variances in human mobility patterns. A recent work by [4] showed that call data records can be organized into profiles and clustered using the spatiotemporal usage characteristics of each profile, allowing for accurate prediction and possible adaptation of the network according to the usage dynamics.…”
Section: Related Workmentioning
confidence: 99%
“…[16] study the spatio-temporal properties of users activities as captured through the inter-checkin times and the inter-checkin distances. They further identify universal features for human urban mobility [15]. In alignment, Cho et al [2] use cell phone location and LBSN data to understand the laws dictating human mobility.…”
Section: Related Workmentioning
confidence: 99%
“…In fact Noulas et al [27] focused on human mobility patterns in a large number of cities. Mobility data have been retrieved from mobile location-based social services.…”
Section: Related Workmentioning
confidence: 99%